Blood HDAC4 Variation Links With Disease Activity and Response to Tumor Necrosis Factor Inhibitor and Regulates CD4+ T Cell Differentiation in Ankylosing Spondylitis - Dou, Bin; Ma, Fuzhe; Jiang, Zhenyu; Zhao, Ling (Frontiers in Medicine, 2022)
Purpose: Histone deacetylase 4 (HDAC4) regulates the progression of autoimmune diseases. This study aimed to further investigate the correlation between HDAC4 and Th cells, inflammation, disease activity, and treatment response in ankylosing spondylitis (AS) patients. Methods: 132 active AS patients were enrolled, of whom 54 patients received TNF inhibitor (TNFi) and 78 patients received NSAID. Serum HDAC4 was measured by ELISA in AS patients before treatment (W0), a week (W)4, W8, and W12 after treatment. Meanwhile, serum HDAC4 was detected in 30 osteoarthritis patients and 30 health controls (HCs) by ELISA. Besides, naïve CD4+ T cells from AS patients were isolated, followed by modulation of HDAC4, then polarization towards Th1, Th2, or Th17. Results: HDAC4 was reduced in AS patients compared to HCs and osteoarthritis patients (both P<0.01). In AS patients, HDAC4 was negatively correlated with TNF (P<0.001), IL-1β (P=0.003), Th17 proportion (P=0.008), C-reactive protein (P<0.001), and ASDAS (P=0.038), but not IL-6, Th1 proportion or other characteristics. Meanwhile, HDAC4 increased from W0 to W12 (P<0.001); HDAC4 at W8 (P=0.014) and W12 (P=0.006) was raised in ASAS40-response patients than ASAS40-non-response patients; further subgroup analysis showed that HDAC4 at W12 was higher in ASAS40-response patients than ASAS40-non-response patients (P=0.016) in TNFi treated group, but not in NSAID treated group. In addition, HDAC4 negatively regulated polarization of naïve CD4+ T cells towards Th17 (P<0.01), but not Th1 or Th2. Conclusion: HDAC4 is associated with lower inflammation and disease activity, negatively regulates Th17 polarization, whose increment after treatment reflects favorable outcomes in AS patients.